Multi‐Photon Microscopy. Issue 1 (27th January 2023) - Sanderson, Jeremy
Abstract: In this series of papers on light microscopy imaging, we have covered the fundamentals of microscopy, super‐resolution microscopy, and lightsheet microscopy. This last review covers multi‐photon microscopy with a brief reference to intravital imaging and Brainbow labeling. Multi‐photon microscopy is often referred to as two‐photon microscopy. Indeed, using two‐photon microscopy is by far the most common way of imaging thick tissues; however, it is theoretically possible to use a higher number of photons, and three‐photon microscopy is possible. Therefore, this review is titled "multi‐photon microscopy." Another term for describing multi‐photon microscopy is "non‐linear" microscopy because fluorescence intensity at the focal spot depends upon the average squared intensity rather than the squared average intensity; hence, non‐linear optics (NLO) is an alternative name for multi‐photon microscopy. It is this non‐linear relationship (or third exponential power in the case of three‐photon excitation) that determines the axial optical sectioning capability of multi‐photon imaging. In this paper, the necessity for two‐photon or multi‐photon imaging is explained, and the method of optical sectioning by multi‐photon microscopy is described. Advice is also given on what fluorescent markers to use and other practical aspects of imaging thick tissues. The technique of Brainbow imaging is discussed. The review concludes with a description of intravital imaging of the mouse. © 2023 Wiley Periodicals LLC.